2020
DOI: 10.3389/fpubh.2020.00363
|View full text |Cite
|
Sign up to set email alerts
|

Considering Work Arrangement as an “Exposure” in Occupational Health Research and Practice

Abstract: Most occupational health research is conducted with the so-called “standard employment relationship” in mind, which entails ongoing, full-time employment for a single employer. Yet mounting evidence suggests the way work is organized is increasingly deviating from this standard model, and that work arrangements themselves—the terms and conditions of employment such as contract type and the extent of directive control over tasks—are important determinants of worker health and safety. However, a lack of clear co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…While examining nonstandard work arrangements is common in the literature, these jobs tend to be heterogeneous in character with little consensus on how to categorize and define them (e.g., contractor jobs include both flexible contract work tailored toward high-skilled workers as well as low-paid gig work). 18 Furthermore, these nonstandard work arrangements may not capture important aspects of precarious employment, such as unbalanced worker-employer power dynamics central to the precarious employment construct. We developed a multidimensional measure to more thoroughly capture precarious employment experiences than a measure of nonstandard work arrangement can provide.…”
Section: <0001mentioning
confidence: 99%
See 3 more Smart Citations
“…While examining nonstandard work arrangements is common in the literature, these jobs tend to be heterogeneous in character with little consensus on how to categorize and define them (e.g., contractor jobs include both flexible contract work tailored toward high-skilled workers as well as low-paid gig work). 18 Furthermore, these nonstandard work arrangements may not capture important aspects of precarious employment, such as unbalanced worker-employer power dynamics central to the precarious employment construct. We developed a multidimensional measure to more thoroughly capture precarious employment experiences than a measure of nonstandard work arrangement can provide.…”
Section: <0001mentioning
confidence: 99%
“…[9][10][11][12][13] Solutions include providing assistive technologies 14 and modifying psychosocial factors, such as co-worker and supervisor support. 15 However, despite the growing prevalence of nonstandard work arrangements and precarious employment in the occupational health and safety discourse, [16][17][18] few studies have investigated the role of nonstandard and precarious jobs in the RTW process. 19,20 Nonstandard work arrangements have become increasingly common in the United States and globally.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 1980s, there has been a growing body of research (hundreds if not thousands of studies) into the health effects of precarious work, job insecurity, and the informal sector. The vast majority of these studies, using an array of methods, have found these work arrangements are associated with worse health outcomes including increased injury frequency rates, adverse physical health/hazard exposures and poor mental health as well as inferior protection under occupational health and safe and workers’ compensation/social security laws ( Quinlan, 2015 ; O’Connor et al , 2020 ). Subcontracting and the precarious work it entails also contributed to disasters in mines and factories, refineries, and oil rigs ( Quinlan, 2014 ).…”
mentioning
confidence: 99%